The Discrepancy between the Algerian Language Policy in Higher Education and Science Students’ Attitudes towards English - MEKROUD, Bilal (Journal of Human Sciences, 2017)
This study focuses attention on the areas of language policy and language attitude in higher education. It aims at examining the relationship between students’ attitudes towards English and the current Algerian language policy in science faculties. The study provides ample evidence that the language policy practices in the Algerian science faculties are not responsive to students’ attitudes and linguistic needs. It also shows that although English is the language of science and technology of this era, French is still the language of teaching and learning of core science subjects in Algeria. Moreover, this attitudinal survey shows that even if students fail to master English, they hold a fairly positive attitude towards it. Students also think that in order to eliminate the linguistic disadvantage they face in the world of academia; actions must be taken by governmental bodies to ensure that English will be the major medium of tuition. The paper also suggests that more measures in the Algerian language-in-education policy should make a paradigm shift towards using English in all the scientific realms to fulfil students’ linguistic needs.